Composition model and method of creation of functionally-oriented information resources - Chucklyaev, I. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
In the paper the composition model of functionally oriented informational resources is provided as well as the method for creating this model. The composition model and method of functionally oriented informational resources provide enhanced features on creation of informational security systems. The composition model corresponds to a data model in not the first normal form, is formed by the functional complex of data and is presented in the form of polybasic algebraic structure which displays structure, correlations, and also specifics of operations of handling and processing over difficult structured data. The method of creation of function-oriented information resources is based on a deductive method of creation of axiomatic theories. The formalized description of function-oriented information resources is provided; the functional complex of data of polybasic algebraic structure of composition model; the functional dependences and the relation forming system of axioms of composition model. Graphic elements on which it is displayed components of subsystems are shown; structurally functional chart of component interaction of levels of control; the structure of composition model of function-oriented information resources provided by the table of difficult structured data in not the first normal form; structural logic circuit of a method of creation of composition model of function-oriented information resources.